Chinese Shaolin kung fu = [Zhongguo Shaolin kung fu - Lu, Hongjun (China Pictorial Pub. House, 2007)
The monks shown in this photo book are actual monks training their discipline at the famed Shaolin Temple in Shaan xi, China. Contrary to what the movies show, not all of these monks are young men, some are ancient codgers, and some are mere boys. But no matter the age, each kung fu master defies gravity and pushes the physical limits of the human body.